Characterization of PbS nanoparticles synthesized using sodium lauryl sulfate at room temperature. (2023) - Chatterjee, Bappaditya; Bandyopadhyay, Amitava
Abstract: Synthesis of lead sulfide (PbS) nanomaterials was carried out via an anionic surfactant-assisted co-precipitation route at room temperature. The anionic surfactant used in this process was Sodium Lauryl Sulfate (SLS). X-ray diffraction (XRD) was carried out for characterizing the synthesized PbS nanoparticles. Peak broadening analysis was done to investigate crystallite size using Scherrer, Williamson-Hall, modified Scherrer, and Size-Strain method. Uniform Deformation Model (UDM) was assumed to calculate lattice strain for all peaks of XRD data of PbS nanoparticles via the Williamson-Hall plot method. The Size-Strain method was also used to estimate strain more accurately. The surface structures of the synthesized PbS nanoparticles were studied by Scanning Electron Microscopy (SEM). The synthesized PbS sample was also analyzed by Fourier Transform Infrared Spectroscopy (FTIR) to ascertain the phases. It was observed that the Size-Strain method gives the most adequate approximation of average particle size having a diameter of 21.29 nm for PbS synthesized with 0.01 M SLS concentration at room temperature.